If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying d + -3 = 5d + 7 Reorder the terms: -3 + d = 5d + 7 Reorder the terms: -3 + d = 7 + 5d Solving -3 + d = 7 + 5d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5d' to each side of the equation. -3 + d + -5d = 7 + 5d + -5d Combine like terms: d + -5d = -4d -3 + -4d = 7 + 5d + -5d Combine like terms: 5d + -5d = 0 -3 + -4d = 7 + 0 -3 + -4d = 7 Add '3' to each side of the equation. -3 + 3 + -4d = 7 + 3 Combine like terms: -3 + 3 = 0 0 + -4d = 7 + 3 -4d = 7 + 3 Combine like terms: 7 + 3 = 10 -4d = 10 Divide each side by '-4'. d = -2.5 Simplifying d = -2.5
| 8x+7=4x-2 | | 4-y=7-2y | | 5+y=8-2y | | X+[2+x]+[4+x]=173 | | 4x-18=7x | | 6k^2+8k+4=0 | | 6p^2-pq-q^2= | | 3(h+7)=2(h+5) | | 8y^2+23y-3= | | =0.03703703703 | | 30z^2-23z+2= | | 8x=9+9x | | 3s+7=11-s | | 5w+2=2w+14 | | (tg(x)+1)*cos(x)=0 | | 200=20+2x | | 4-2r=3-r | | x+18=2x+12 | | -x=16-5x | | 12x+6y=432 | | 7x+24=3x | | 5a-3/2a= | | (x^2-x+1)(x^2+x+1)= | | h+7=4h-5 | | (10-(3x-7)-8x)=-14 | | 2=4X/X | | 6b+10=16+4b | | 9x+9.33=6x+15 | | 3q+11=3+4q | | 9u^2+24uv+16v^2= | | 0=(2p^2q^2)(49p^2q^10) | | 2f+9=3f-15 |